PENDAMPINGAN TUMBUH KEMBANG ANAK USIA DINI DI PAUD - Wiwin Rohmawati (WASATHON Jurnal Pengabdian Masyarakat, 2026)
Child growth and development and early childhood education are a concern for the government. According to the results of research in the field of neurology such as that carried out by Dr. Benyamin S. Bloom, an education expert from the University of Chicago, United States, stated that brain tissue cell growth in children aged 0-4 years reaches 50%. This means that if at that age the child's brain does not receive maximum stimulation, all of the child's growth and development, both physical and mental, will not develop optimally. The family environment can be an important pattern in cultivating national character for children and the younger generation. On that basis, character education does not just teach what is right and what is wrong, more than that, character education instills habits (habituation) about what is good so that children become understanding (cognitive) about what is right and wrong, able to feel (affective) good values ​​and habitually do them (psychomotor). In other words, good character education must involve not only aspects of "good knowledge" (moral knowing), but also "feeling well" (moral feeling) and "good behavior" (moral action). Character education emphasizes habits or habits that are continuously practiced and carried out [1]. Therefore, this service is needed as an effort to assist parents in the growth and development of early childhood. First, structured education by educators with material on child development. Second, the introduction of early childhood growth and development instruments using information sheets containing developments according to the child's age. This information sheet can be used by parents while at home. The goal is that parents can find out developments according to age.